SEANERGY - a spatial tool to facilitate the increase of synergies and to minimise conflicts between human uses at sea. (October 2020) - Bonnevie, Ida Maria; Hansen, Henning Sten; Schrøder, Lise
Abstract: With expanding human uses at sea, the objective of maritime spatial planning (MSP) to promote sustainable coexistence between marine uses becomes an increasingly challenging task. In order to assess coexistence options, both use-use interactions and use-environment interactions are important to explore. Tools for doing cumulative impact assessments (CIA) on the environment provide a means for spatially exploring environmental impacts. Finding inspiration in such ecosystem-based spatial use-environment approaches while drawing on pairwise marine use compatibility knowledge from existing literature, a spatial approach to model potential synergies and conflicts between marine uses through an expert-based scoring system is presented and implemented in SEANERGY, an ArcMap-based opensource toolbox. A test based on Baltic Sea GIS-data demonstrates how SEANERGY supplements CIA analyses with knowledge about potential use-use synergies, potential use-use conflicts, and their spatial extents, useful for optimising the use of marine space in MSP without putting too much cumulative pressure on the environment. Graphical abstract: Image 1 Highlights: A GIS-approach for sustainable coexistence in Maritime Spatial Planning (MSP) is introduced. The novel spatial approach is implemented in the GIS-tool SEANERGY. SEANERGY facilitates options to increase synergies and decrease conflicts between marine uses. Results analysing the Baltic Sea demonstrate how SEANERGY facilitates co-location analyses. SEANERGY can advantageously be combined with cumulative impact assessments (CIA) on the environment.